An alternative source for contemporary public administration: aspects of public service employment in classic Jewish tradition - Schnall, David J. (1997)
Jewish cultural sources include scriptural narrative, Talmudic discourse, legal and ethical code, case law, and municipal regulation, developed over some 4 millennia of recorded history under a broad variety of diverse social and political circumstances. Nevertheless, they are rarely invoked as sources for the study of contemporary public administration. A review of normative Jewish thought may uncover long-dormant insights and inferences at variance with those rooted elsewhere. It further may set the stage for analysis of other national-cultural precedents and add to the diversity that informs the field. This article analyzes Jewish tradition relative to its consideration of public service and human resource issues regarding tenure and job security, collective bargaining, and accountability for quality assurance. - Reproduced
Keywords: Civil service